The Role of the Government and Food Price Dynamics in East Java: A Comparison of 2023-2025 - Iswahyuni, Deviana; -, Fahrurrozi; Addainuri, Muhammad Isbad (Public Policy, 2025)
The persistent rise in staple food prices presents a strategic challenge that affects community welfare, particularly in East Java as a central hub of national food distribution. This study employs a descriptive qualitative approach using secondary data from SISKAPERBAPO (2023–2025) to analyze the government's role in food price stabilization through allocation, distribution, and stabilization functions. The findings reveal that climatic conditions, seasonal demand, and uneven distribution contribute significantly to price fluctuations. In response, government interventions such as market operations, subsidies, and policies promoting sustainable production and equitable distribution are essential in maintaining food price stability, enhancing food security, and managing regional inflation. Thus, effective and continuous policy coordination is necessary to ensure stable access to affordable staple foods.